Booklet development based on identification of medicinal plants in cempaka lake and hill, kebumen regency - Darmawan, Ericka; Christiyani Kusumaningrum, Serafica Btari; Yufita, Andira (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to develop information media in the form of a booklet of medicinal plants found in Cempaka Lake and Hill, how to use medicinal plants for traditional medicine, assessing the feasibility of the developed booklet, and the community's response to the developed booklet. The research method used is Exploration and R&D (Research and Development) with the ADDIE development model, which consists of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. Based on the results of exploration by walking along the hiking trail via Purwonegoro Banjarnegara, and the hiking trails via Sempor, and Kebumen, 21 species of medicinal plants were identified which were grouped into 7 classes including Magnoliopsida, Liliopsida, Lycopodiinae, Dycotyledoneae, Angiospermae, Monocotyledonae, and Asteridae. Methods for processing medicinal plants include boiling, pounding, brewing, grating, crushing, and also without processing (used directly). The developed booklet is included in the very valid category with an average percentage of 83.3% on the material aspect validity assessment and 97.72% (very valid) on the media aspect validity assessment. The community's response results showed that the booklet was convenient to use with an average total percentage of 95.93% (very feasible category) used as a source of information for around Cempaka Lake and Hill.